Error Bounds for a Fictitious Domain Method with Lagrange Multiplier Treatment on the Boundary for a Dirichlet Problem - Pan, Tsorng-Whay (Japan journal of industrial and applied mathematics, 1998)
In this article we obtain discrete inf-sup conditions and error bounds for a fictitious domain with Lagrange multiplier treatment for the boundary condition on the curved boundary to an elliptic Dirichlet problem with conforming finite elements of degree one on a uniform mesh.[PUBLICATION ABSTRACT]